2016
DOI: 10.1002/ejlt.201400334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet supplementation with chia (Salvia hispanica L.) oil and natural antioxidant extract on the omega‐3 content and antioxidant capacity of Nile tilapia fillets

Abstract: In this study, the effect of adding chia oil and avocado extract to the diet of Nile tilapias (Oreochromis niloticus) was evaluated after 0, 15, 30 and 45 treatment days. The inclusion of chia oil and avocado extract aims to nutritional enrichment of fish fillet by the use of a new lipid source and a by‐product of low cost and high antioxidant capacity. Thus, experimental diets were formulated by the addition of 0.14% of ethanolic extract of avocado peel (Treatment I), 1.90% of chia (Salvia hispanica L.) oil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…However, although there was no significant difference between the TL values of the two treatments after 30 days, the Nile tilapias fed with the supplemented diet (TII) grew more and gained more weight to those fed with the control diet (TI). Arslan et al 48 and Montanher et al 37 also reported this behavior, i.e., the fish preference for diets supplemented with LNA.…”
Section: Growth Weight Gain and Total Lipids Of Nile Tilapiamentioning
confidence: 77%
See 2 more Smart Citations
“…However, although there was no significant difference between the TL values of the two treatments after 30 days, the Nile tilapias fed with the supplemented diet (TII) grew more and gained more weight to those fed with the control diet (TI). Arslan et al 48 and Montanher et al 37 also reported this behavior, i.e., the fish preference for diets supplemented with LNA.…”
Section: Growth Weight Gain and Total Lipids Of Nile Tilapiamentioning
confidence: 77%
“…36 Fatty acid methyl esters (FAME) were determined by gas chromatography (GC), using a routine analysis method previously developed in our laboratory. [37][38][39][40][41] GC analysis was carried out using a Thermo™ model TRACE ultra 3300 fitted with a flame ionization detector (FID) and a fused-silica CP-7420 (Select™ FAME)…”
Section: Fatty Acid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These unique characteristics give oils from camelina and chia advantage over previously used terrestrial sources, making them well suited for industrial use with potential benefits for both fish and humans through healthy diets. Earlier studies have shown that dietary inclusion of camelina and chia oils did not negatively affect growth performance in Nile tilapia (Carbonera et al., 2016; Montanher et al., 2016), rainbow trout (Hixson, Parrish, & Anderson, 2014a), Atlantic salmon (Hixson, Parrish, & Anderson, 2014b) and Atlantic cod (Hixson & Parrish, 2014; Morais, Edvardsen, Tocher, & Bell, 2012). In addition to this, fatty acid profiles of fish fed such diets showed increased n‐3 PUFA contents.…”
Section: Introductionmentioning
confidence: 95%
“…A tilápia é um alimento detentor de excelentes propriedades nutricionais (composição proteica equilibrada, lipídios essenciais, vitaminas, sobretudo as lipossolúveis, e minerais) (HERNÁNDEZ-SÁNCHEZ e AGUILERA-MORALES, 2012). Tais propriedades podem ser melhoradas por meio da incorporação de nutrientes advindos da dieta fornecida às tilápias, como mostrado em diversos estudos que incorporaram diferentes suplementos, em sua maioria fontes de ácidos graxos, vitaminas e antioxidantes (NAVARRO et al, 2012;LOPES et al, 2015;CARBONERA et al, 2014CARBONERA et al, , 2016MONTANHER et al, 2016;BONAFÉ et al, 2017).…”
Section: Introductionunclassified